2015
DOI: 10.5505/sakaryamj.2015.03360
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Chondromalacia Patella and Subcutaneous Knee Fat Thickness: A Study With Magnetic Resonanve Imaging

Abstract: Amaç: Bu çalışmadaki amacımız obezitenin göstergesi olan prepatellar subkutan yağ kalınlığı (PSYK) ile kondromalazik patellanın (KP) varlığı ve şiddeti arasındaki ilişkiyi belirlemektir. Gereç-Yöntem: Retrospektif olan bu çalışmaya 9 aylık dönemde çeşitli nedenlerle diz manyetik rezonans görüntüleme (MRG ) yapılan ve kritelere uyan 175 hasta dahil edildi. Çekimler 1.5 T MRG cihazında ekstremite koili kullanılarak yapıldı. KP değerlendirmesi için aksiyal kesitler kullanıldı ve grade 0 ( normal) ile grade 3 (kom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…The authors reported that PSFTT was higher in the CP group than in the control group, a positive correlation was found between PSFTT and CP (r = 0.47), and thicker SFTT was observed in women than men. 13 The results of the present study were very similar to both of these studies and underlined the main results. In addition, when compared with the results of previous studies, the PSFTT measurements in the present study indicated a stronger correlation between SFTT and the CP grade.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The authors reported that PSFTT was higher in the CP group than in the control group, a positive correlation was found between PSFTT and CP (r = 0.47), and thicker SFTT was observed in women than men. 13 The results of the present study were very similar to both of these studies and underlined the main results. In addition, when compared with the results of previous studies, the PSFTT measurements in the present study indicated a stronger correlation between SFTT and the CP grade.…”
Section: Discussionsupporting
confidence: 90%
“…Women had higher SFTT values than men. 14 Duran et al 13 studied 175 patients and measured PSFTT to identify any relationship with CP. The authors reported that PSFTT was higher in the CP group than in the control group, a positive correlation was found between PSFTT and CP (r ¼ 0.47), and thicker SFTT was observed in women than men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified Noyes classification was used to categorise the cartilage damage for the patients with CP, similarly as that used in knee MRI studies in the literature [ 13 , 14 ]. According to this method, grade 0 showed normal articular cartilage with homogenous signal intensity with an intact surface and thickness, grade 1 indicated a normal cartilage surface but focal abnormal signal intensity, grade 2 represented a defect less than 50% of the cartilage thickness (2A) or a cartilage defect more than 50% thickness but less than a full thickness (2B), and grade 3 specified a full cartilage thickness defect with exposed bone ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%